Harnessing the Force Generated by Nanoscale Enzymes to Power Active Motion of µ - sphere - Veerpal Kaur (My University, 2025)
Living systems harness energy from their surroundings to achieve complex movements, such as simultaneous rotation and translation. This capability is particularly evident in microorganisms like Chlamydomonas and Volvox, which navigate challenging environments with remarkable precision. These biological active systems achieve self-propulsion via various swimming mechanisms, such as the use of rotating flagella, cilia, or the peculiar amoeboid motion used by eukaryotic cells to crawl or swim. In the biological world at every level, we will find a huge number of active systems such as molecular motors (ATP-consuming machines) at the nano scale, sperm cells, shape transformation in cells at the cellular level, and green algae motion (Volvox) at the multi-cellular level, school of fishes at macro scale etc. Inspired by nature, to date, many nano/micron-sized non-living active particles have been synthesized. These active particles can move on their own or by use of an external energy source like a magnetic field, sound waves (acoustic-driven particles), chemical reactions like H2O2 decomposition (gas propulsion), exothermic reaction (rise temperature gradient), electrochemical reactions (generate ion gradient), light source (photothermal effects), and induce isomerization (photochromic). Even with significant advancements in the field of nano/micro scale active systems, their use in biomedical applications like drug delivery or blood clot repair remains unattainable. The primary constraints are their size, poor biocompatibility of the fuels for active motion, as well as materials used for fabrication and their mobility in biological fluids. Enzymes are excellent candidates for use as catalysts because of their high turnover numbers, excellent selectivity in physiological conditions, and biocompatibility. Recent studies revealed that enzymes while catalysing, can produce enough mechanical force to move themselves or the chassis material, they are attached to. In this study, we introduce a design principle for achieving simultaneous spinning and linear motion in biocompatible chassis material. For the chassis, we employed lipid vesicles. Flexible enzymes undergoing cyclic, conformational change with substrate supply, drive the mechanical work. Leveraging transient interactions, we induce spontaneous symmetry-breaking in enzyme distribution on GUVs, enabling diverse movements from pure spinning to spiral 3D trajectories. Overall, we proposed that clusters of flexible enzymes distributed anisotropically on any rigid chassis material can generate tangential shear stress and execute emergent kinematics from pure rotational to gyrational
Keywords: Generated by Nanoscale; Motion